The Bibliometric Analysis of Fraud Reporting: Scientific Publications from 2019 to 2024 - Fajriyati, Sausan; Yusuf, Muhammad (The Future of Education Journal, 2025)
This study aims to analyze the development of scientific publications related to fraud reporting during the period of 2019–2024. Using a quantitative method based on a bibliometric study approach, data was collected from the Scopus database with the keywords "fraud" and analyzed using R Studio and VOSviewer software. The results indicate that 666 documents were published, involving 1,828 authors from 81 countries. The United States emerged as the country with the highest publication contribution, followed by Indonesia. The analysis shows that the topic of fraud reporting is closely associated with key terms such as fraud detection, corporate governance, blockchain, and financial reporting, which are strongly connected in the global research network. Keyword and trend visualization indicate a growing focus on modern technology, corporate governance, and the role of whistleblowing. This study provides a comprehensive insight into the development of fraud reporting research while identifying research gaps that can serve as references for future studies.